2018
DOI: 10.2175/106143017x15131012152753
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and Metabolism of Tetrabromobisphenol A (TBBPA) in the Bioaugmented Activated Sludge Batch Bioreactor System by Heterotrophic and Nitrifying Bacteria

Abstract: Tetrabromobisphenol A [2,4'-isopropylidenebis(2,6-dibromophenol)] has been identified in wastewater samples collected from the Guelph municipal wastewater treatment plant (GWWTP). In order to assess the kinetics and metabolic mechanisms of the dissolved TBBPA, bench scale experiments were completed with batch bioreactors. The biodegradation test was conducted by taking aerobic sludge from the conventional activated sludge reactor (CAS) and membrane bioreactor (MBR), and bioaugmenting both reactors with soil ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Therefore, I. lacteus F17 is expected to be a good candidate for degrading TBBPA. Previous studies have demonstrated that TBBPA can be degraded by aerobic and anaerobic bacteria in sewage, soil, activated sludge and sediments, and the mechanism of bacteria degrading TBBPA has been wellknown [17,18,29], little work has been done to elucidate the biodegradation characteristics and mechanisms of TBBPA by white-rot fungus.…”
mentioning
confidence: 99%
“…Therefore, I. lacteus F17 is expected to be a good candidate for degrading TBBPA. Previous studies have demonstrated that TBBPA can be degraded by aerobic and anaerobic bacteria in sewage, soil, activated sludge and sediments, and the mechanism of bacteria degrading TBBPA has been wellknown [17,18,29], little work has been done to elucidate the biodegradation characteristics and mechanisms of TBBPA by white-rot fungus.…”
mentioning
confidence: 99%
“…Oxic environments often favor micropollutant degradation compared to anaerobic settings, including TBBPA (McAvoy et al, 2016;Ghattas et al, 2017). Activated sludge is the main aerobic system investigated in TBBPA biotransformation as the primary (TBBPA-conversion) (McAvoy et al, 2016;Islam et al, 2018) or the secondary (BPA-conversion) strategy (Ronen and Abeliovich, 2000). The influence of different additives on TBBPA degradation by aerobic consortia has been investigated as much as for anaerobic communities (Table 1.1) and with similar results, suggesting that the degradation of TBBPA in aerobic environments is also driving by co-metabolic processes biostimulated by exogenous carbon sources.…”
Section: Aerobic Reactorsmentioning
confidence: 99%
“…The biological degradation of halogenated micropollutants is assumed to be possible under all redox conditions by a variety of bacterial and archeal species (Hardman, 1991;Peijnenburg et al, 1992;Haggblom, 1992;Fetzner, 1998;Ghattas et al, 2017). In bioreactors, TBBPA degradation by microbial species has been investigated over the past 20 years, aiming at optimizing bioprocesses mostly by evaluating operational parameters (pH, temperature, concentration, carbon source, and other amendments) and understanding isolated bacterial strain functions (Ronen and Abeliovich, 2000;Iasur-Kruh et al, 2010;Chang et al, 2012;Yang et al, 2016;Fan et al, 2017;Islam et al, 2018;Cheng et al, 2019;Lefevre et al, 2019;Lin et al, 2020). Nearly all studies on TBBPA bioconversion have been conducted at high concentrations, compared to its environmental occurrence (in ng L -1 or µg L -1 ), and by pure or enriched cultures under laboratory settings, which are too far from environmentally relevant conditions, but provide crucial insights into the metabolic mechanisms of TBBPA bioconversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation